Novel asymmetrical oxime ligand-based coordination compounds in conducting copolymer as a useful electrodes for electrochemical supercapacitors - Kalyon, Hilal Yildirim; Basili, Taskin; Gencten, Metin; Macit, Mustafa; Sahin, Yucel (SPRINGER HEIDELBERG, 2025)
The combination of oxime compounds with conducting polymers shows great potential in improving supercapacitor technology. This research examines the combined impacts of oximes and copolymers in composite electrodes by systematically exploring electrochemical methods. At the first stage of this work, novel Vic-dioxime-based oxime compounds were synthesized and named as [Ni(LoxH)2], [Cu(LoxH)2] and [Co(LoxH)2].2H2O. They were incorporated into copolymer matrices through electrochemical way simultaneously with copolymer production. Analysis of the electrode materials through spectroscopic (FT-IR), microscopic (SEM-EDS) and electrochemical techniques (cyclic voltametric scan rate optimization, galvanostatic charge-discharge tests at different currents, long-cycle stability test and electrochemical impedance spectroscopy before extended cycling) provided insights into the structural and electrochemical characteristics of the composites. Areal capacitances at 10 mV s-1 were determined as 488.4 mFcm-2, 286.0 mFcm-2 and 260.9 mFcm-2 for [Cu(LoxH)2]@PGE/(PAn-co-PPy), [Ni(LoxH)2]@PGE/(PAn-co-PPy) and [Co(LoxH)2]@PGE/(PAn-co-PPy), respectively. Capacitance retention was 95% at the end of 1000 cycle in [Cu(LoxH)2]@PGE/(PAn-co-PPy) electrode.
Keywords: Electrochemical supercapacitors; Conducting copolymers; Organic ligands; Metal complexes; TRANSITION-METAL-COMPLEXES; HIGH-PERFORMANCE ELECTRODE; VIC-DIOXIME LIGAND; REDOX PROPERTIES; ELECTRICAL-CONDUCTIVITY; POLYANILINE; CHEMISTRY; SPECTROSCOPY; MONONUCLEAR; POLYPYRROLE; Electrochemistry; Physics